The EFFECT OF CORN STALKS COMPOST AND RABBIT URINE ON THE CHEMICAL PROPERTIES ( N, P, K) OF ULTISOLS : PENGARUH PEMBERIAN KOMPOS BATANG JAGUNG DAN URIN KELINCI TERHADAP SIFAT KIMIA TANAH ( N, P, K) ULTISO - Nurul Puspita Palupi; Hadi Pranoto; Muhammad Solikin (Universitas Widya Gama Mahakam, 2021)
This study aims to determine the best dose in the use of organic fertilizer compost from corn stalks and rabbit urine, to increase the chemical fertility of Ultisols. This research is an experiment in polybags arranged in a completely randomized non factorial design with eight treatments and four replications. Corn stalk compost treatments are K0 = control K1 = compost 100 g. kg-1, K2 = compost 200 g. kg-1, K3 = compost 300 g. kg -1, and POC rabbit urine treatment U1 = urine 25 mL. L-1 water, U2 = urine 50 mL. L-1 water, U3 = urine 75 mL. L-1 water, U4 = urine 100 mL. L-1 water. Statistical analysis to determine the level of change in nutrient content was carried out using ANOVA (Analysis of Variance) with a level of 5%, if F count is greater than F table 5% then a further test is carried out using the DMRT (Duncan Multiple Range Test). The use of corn stalk compost and rabbit urine POC given on ultisols had a positive effect and corn stalk compost with a dose of 300 g and rabbit urine POC with a dose of 300 mL was the highest.The results showed that the application of corn stalk compost and rabbit urine POC could increase nutrients in ultisols so that it could be developed further.